Analysis of Voltage Transfer Characteristics of Nano-scale SOI CMOS Inverter with Variable Channel Length and Doping Concentration - A. Daniyel Raj; C. Rajarajachozhan; Sanjoy Deb (Журнал нано- та електронної фізики)
During many decades, continuous device performance improvement has been made possible only through device scaling. But presently, due to aggressive scaling at the sub-micron or nanometer region, the conventional planner silicon technology is suffering from the fundamental physical limits. Such imposed limits on further downscaling of silicon planner technology have lead to alternative device technology like Silicon-On-Insulator (SOI) technology. Due-to some of its inherent advantages, the Silicon-On-Insulator (SOI) technology has reduced the Short-channel-effects (SCEs) and thus increased transistor scalability. Till now, intense research interests have been paid in practical fabrication and theoretical modeling of SOI MOSFETs but a little attention has been paid to understand the circuit level performance improvement with nano-scale SOI MOSFETs. The circuit level performance analysis of SOI MOSFET is highly essential to understand the impact of SOI technology on next level VLSI circuit and chip design and for doing so device compact models are high on demand. In such scenario, under present research, a physics based compact device model of SOI MOSFET has been developed. At the first phase of the compact model development, a physics based threshold voltage model has been developed by solving 2-D Poisson’s equation at the channel region and at the second phase, a current-voltage model has been developed with drift-diffusion analysis. Different SCEs, valid at nano-scale, are effectively incorporated in threshold voltage and Current-Voltage model. At the third phase, using the compact model, the Voltage Transfer Characteristics (VTC) for a nano-scale SOI CMOS inverter has been derived with graphical analysis. The impacts of different device parameters e.g.; channel length and channel doping concentration on VTC has been investigated through simulation and the results have been analyzed.